Identification and Characterization of Phospholipase D Genes Putatively Involved in Internal Browning of Pineapple during Postharvest Storage - Hong, Keqian; Zhang, Lubin; Zhan, Rulin; Huang, Bingyu; Song, Kanghua; Jia, Zhiwei (Frontiers in Plant Science, 2017)
Phospholipase D (PLD) in plants plays vital roles in growth, development, and stress responses. However, the precise role of PLDs in pineapple remains poorly understood. In this study, 10 putative PLD genes, designated as AcPLD1–AcPLD10, were identified based on the pineapple genome database. The 10 AcPLDs could be clustered into five of the six known PLD families according to sequence characterization. Their deduced amino acid sequences displayed similarities to PLDs from other plant species. Expression analyses of PLD mRNAs from pineapple pulp were performed. The 10 PLDs exhibited differential expression patterns during storage periods of fruits treated with hexaldehyde (a specific PLD inhibitor) which could alleviate internal browning (IB) of pineapple after harvest. Functional subcellular localization signalling assays of two PLD proteins (AcPLD2 and AcPLD9) were performed by fluorescence microscopy. To further detect the potential action mechanism underlying PLD involved in the IB defense response, PLD, hydrogen peroxide (H2O2) and H2O2 associated with antioxidative enzymes such as superoxide dismutase, catalase, NADPH and ascorbate peroxidase were quantified by enzyme-linked immunosorbent assay. This report is the first to provide a genome-wide description of the pineapple PLD gene family, and the results should expand knowledge of this family.